Relationship Of Incidence Of Frailty With Metformin Consumption Habits In Elderly Type-2 Diabetes Mellitus Patients. - Irwanto, Agus; Ardinata, Dedi; Malisie, Ririe Fachrina (Program Studi Pendidikan Biologi, 2023)
Type 2 diabetes (T2DM) was characterised with insulin resistance and deficiency, furthermore with advancing age the was also an increase in insulin resistance. Clinical studies has proven that insulin resistance and T2DM increase the incidence of frailty syndrome in the elderly. Oral antidiabetics metformin was associated with the inhibition of aging process. Eventhough, there was limitless literature and theorical that showed the relationship of metformin therapy to frailty syndrome. This study aimed to explore the possibility of metformin protective effect on frailty syndrome. This research method uses structured descriptive analysis with literature review. Article Data both original article, research article, Review article and case report are collected to be analyzed in accordance with the purpose of the title and writing of this article. Type 2 Diabetes mellitus is characterized by insulin resistance and deficiency which had happened several decades earlier, in addition to the incidence of insulin resistance will also increase. On some clinical studies that have been conducted, insulin resistance and type 2 Diabetes mellitus, it has been shown to increase the number of occurrences of frailty syndrome in old age. Conclusion Metformin was shown to have protective effect against frailty syndrome in elderly diabetic